The Response of Teenage Anxiety to Parents Wishes in Dead Poets Society (1989) and Negeri 5 Menara (2012) - Mira Puspita Sari, Anjani; Sari, Ulyati Retno (Humanis; Vol 28 No 1 (2024)DO - 10.24843/JH.2024.v28.i01.p05, 2024)
This study examines parent-teen relationships in 'Dead Poets Society' and 'Negeri 5 Menara,' two influential movies from Western and Indonesian cultures. The research investigates how diverse social and cultural norms influence family values and the resolution of common issues. It specifically focuses on the psychological consequences of repressive and authoritarian parenting styles on central characters Neil and Alif, using Sigmund Freud's psychoanalytic theory as a framework. Employing descriptive qualitative analysis and extensive literature and film documentation, the study uncovers distinct anxiety manifestations in Neil (fear) and Alif (depression). Additionally, it highlights the role of unconscious defense mechanisms in dealing with anxiety. This research underscores the universal impact of authoritarian parenting on adolescent mental health and the unique coping mechanisms individuals develop when faced with such stressors.